Landasan Filosofis, Sosiologis dan Yuridis terhadap Positivisasi Perceraian di Pengadilan Agama - Akhmad Farroh Hasan (Universitas Sebelas Maret, 2022)
According to Islamic law, divorce can occur on one side, namely the husband saying Thalaq. but in the KHI article 115 and the Marriage Law Article 39 paragraph (1) of the Marriage Law that